Size and composition dependent structural investigations on Nd1-xBaxCoO3(x = 0.2, 0.3 and 0.4) perovskite cobaltites using X-ray diffraction - Kumar D.; Prajapati P.; Jena P.; Singh A.K. (My University, 2025)
The perovskite materials having general formula ABO3 are widely studied due to their interesting physical properties. The physical properties of the perovskites strongly depend on the particle size and chemical compositions. Here, we present crystallite size and composition dependence of the structural property of Nd1-xBaxCoO3 perovskites. The powder samples of Nd1-xBaxCoO3 perovskites with x = 0.2, 0.3 and 0.4 were prepared by glycine-nitrate auto-combustion technique. The room temperature structural analysis of the studied samples was carried out by Rietveld structure refinement of the X-ray diffraction (XRD). The Rietveld structure refinement of the XRD data reveals that Nd1-xBaxCoO3 perovskites crystallize into two crystallographic phases; tetragonal crystal structure with P4/mmm space group and orthorhombic structure with Pbnm space group. The values of the unit cell lattice parameters and volume strongly depend on the composition and crystallite size. The average values of lattice strain and crystallite size of the prepared nano samples were evaluated using the Williamson-Hall (W-H) technique. © 2019 Elsevier Ltd.